1997
DOI: 10.1126/science.277.5322.112
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effects of Combined Antiretroviral Therapy on CD4 + T Cell Homeostasis and Function in Advanced HIV Disease

Abstract: Highly active antiretroviral therapy (HAART) increases CD4(+) cell numbers, but its ability to correct the human immunodeficiency virus (HIV)-induced immune deficiency remains unknown. A three-phase T cell reconstitution was demonstrated after HAART, with: (i) an early rise of memory CD4(+) cells, (ii) a reduction in T cell activation correlated to the decreasing retroviral activity together with an improved CD4(+) T cell reactivity to recall antigens, and (iii) a late rise of "naïve" CD4(+) lymphocytes while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

65
935
10
27

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,700 publications
(1,037 citation statements)
references
References 30 publications
65
935
10
27
Order By: Relevance
“…The T cell response was characterized by an early rise of naive and memory cells both in CD4 1 and CD8 1 T cells. In previuos studies designed to characterize the HAART-induced T cell repopulation in patients with advanced HIV disease, an increase of CD4 1 naive T cells was observed beginning from 6 to 12 months of therapy [2,3,23]. The faster increase in CD4 1 naive cells observed herein could be explained by a lesser HIV-induced blockade of T cell renewal occurring in patients with moderate immunodeficiency as well as to a more preserved thymic tissue [24].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The T cell response was characterized by an early rise of naive and memory cells both in CD4 1 and CD8 1 T cells. In previuos studies designed to characterize the HAART-induced T cell repopulation in patients with advanced HIV disease, an increase of CD4 1 naive T cells was observed beginning from 6 to 12 months of therapy [2,3,23]. The faster increase in CD4 1 naive cells observed herein could be explained by a lesser HIV-induced blockade of T cell renewal occurring in patients with moderate immunodeficiency as well as to a more preserved thymic tissue [24].…”
Section: Discussionmentioning
confidence: 54%
“…However, in spite of intense investigation, the mechanisms underlying HAART-induced immune reconstitution remain to be fully characterized. Initial studies performed on HIV-1 infected patients with advanced disease suggested that HAART-induced T cell repopulation was mainly due to an early recirculation of memory cells from lymphoid tissues to blood, accompanied by a slow production of newly generated naive T cells [2,3]. More recently, a correlation between the size of thymic tissue and the magnitude of naive T cell recovery after HAART has been demonstrated, suggesting a critical role for the thymus in lymphocyte restoration [4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that HAART induces an improvement in CD4 + T-lymphocyte reactivity for clinically relevant pathogens [3,4,17]. However, the restoration of antigen-specific T-lymphocyte responses was closely related with an increase in CD4 + T-lymphocyte numbers [17] and was associated (in the majority of cases) with a suppression of viral load.…”
Section: Discussionmentioning
confidence: 98%
“…This decrease is associated with a progressive impairment of immune function. Highly active antiretroviral therapy (HAART, including at least 1 protease inhibitor [PI]), allows for a significant decrease in plasma and tissue HIV-1 RNA load, as well as a quantitative recovery of peripheral CD4 + T-lymphocytes in the majority of adults with HIV-1 infection [2][3][4][5] resulting in a significant reduction in morbidity and mortality [6]. However, the mechanisms governing immune improvement under HAART are still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it remains an open question concerning whether MG is an autoimmune disease that occurs in the thymus owing to a thymic autoantigen or is a systemic autoimmune disease with peripheral immune cell trafficking to the thymus. to rises in CD4 +, CD45RA § (putative naive) T cells (53)(54)(55). However, antiretroviral therapyinduced CD4+ T cell rises do not usually reach normal pre-HIV-1 infection levels.…”
Section: And 7)mentioning
confidence: 99%